THE IMPLEMENTATION OF ISLAMIC EDUCATION TEACHERS’ COMPETENCY QUALITY IMPROVEMENT PROGRAM AT MADRASAH IN ACEH TAMIANG - Sulaiman Sulaiman; Fachruddin Azmi; Chandra Wijaya (State Islamic University of North Sumatra Indonesia, 2019)
This research aims to demonstrate the implementation of Islamic Education Teachers’ Competency Quality Improvement Program at Madrasah in Aceh Tamiang Regency, Nangroe Aceh Darussalam. Teachers’ quality improvement become a significant program that should be implemented by stakeholders of education especially in Islamic education such as Madrasah. It is because quality improvement of teachers underpin the successful of education. In reality, quality improvement effort for Islamic teachers is still applied in low frequency, it is because the attention to this problem by stakeholders of education is still far from the purposes. Therefore, it is needed some real activity such as quality improvement of Islamic education teacher to held applied in solving this problem. The research is done in Aceh Tamiang regency in which the reason is that the majority people in this regency are Muslim, therefore, Islamic education become a specific site that need to be recognized to go forward. This is qualitative research which data finding are explained descriptively by showing the real evidences from finding. As the result, the implementation of Islamic education teachers’ competency quality improvement need to be applied with its rule. The role of teachers Islamic education become one of important thing that need to be recognized in order to get better in the future Islamic education. Keywords: Teachers’ competency quality, Madrasa, Aceh Tamiang